OS DESAFIOS E PERSPECTIVAS DO DIREITO SOBRE A ÓTICA DAS POLÍTICAS PÚBLICAS EM DEFESA DO PANTANAL - SOUZA, Ulysses Alves Cabral Cavalcante,; PINHEIRO, Marina Ferreira Soares,; SILVA, Guilherme Pinheiro, (ANAIS DO ENIC, 2024)
-